Assessing the Construct Validity of the Chinese-Version Schizotypal Personality Questionnaire-Brief on Male and Female Undergraduate Students. Issue 2 (June 2015) - Ma, Wei-Fen; Lane, Hsien-Yuan; Chiang, Li-Chi; Wu, Po-Lun; Yang, Shu-Ju; Tsai, Guochuan E.
Abstract Background: Screening for the schizotypal personality trait is one strategy to identify people who may be susceptible to early psychosis or be at high risk for prodromal psychosis. The Schizotypal Personality Questionnaire-Brief (SPQ-B) has been widely used to assess the schizotypal personality and has been translated into Chinese. However, the psychometric properties of the Chinese-version scale have yet to be evaluated. Purpose: This study evaluates the construct validity of the Chinese-version SPQ-B on a sample of male and female undergraduate students in Taiwan. Methods: A cross-sectional design with convenient sampling was used for this study. The data were collected using the Chinese-version SPQ-B between October 2008 and June 2009. Participants included 513 male and 675 female undergraduate students in Taiwan. The factor construct validity of the scale was examined by confirmatory factor analysis using structural equation modeling with SPSS AMOS version 17 software. Results: The results show that the three-factor model fits the data better than the one-factor model for both male and female participants. The male participants scored significantly higher than their female counterparts in terms of total scale, interpersonal subscales, and disorganized subscales. Conclusions/Implications for Practice: The Chinese version of the SPQ-B adequately achieves three-factor construct validity for undergraduate students. The scale may be used to screen for the schizotypal personality trait in both male and female college students to identify those at an elevated risk for mental illness.